The Amino Acid Sequence of a Major Nonimmunoglobulin Component of Some Amyloid Fibrils - Levin, Mark (1972)
The complete amino acid sequence of a protein, acid soluble fraction, (ASF) which constitutes up to 50% of amyloid fibrils from a patient with familial Mediterranean fever has been obtained. Partial amino acid sequences of three other proteins from patients with secondary amyloidosis were identical in the regions studied except for an alanine-valine interchange in one. The ASF contains no cysteine, does not resemble any known immunoglobulin, and has not been detected as yet in myeloma-associated amyloid.